Rhipicephalus simus ticks: new hosts for phleboviruses - Samuel Munalula Munjita; Benjamin Mubemba; John Tembo; Mathew Bates; Sody Munsaka; Ala Tabor (Parasitology)
Ticks are widespread arthropods that transmit microorganisms of veterinary and medical significance to vertebrates, including humans. Rhipicephalus simus, an ixodid tick frequently infesting and feeding on humans, may play a crucial role in transmitting infectious agents across species. Despite the known association of many Rhipicephalus ticks with phleboviruses, information on R. simus is lacking. During a study in a riverine area in Lusaka Zambia, ten R. simus ticks were incidentally collected from the grass and bushes and subjected to metagenomic next generation sequencing (mNGS) in 2 pools of 5. Analysis detected a diverse microbial profile, including bacteria 82% (32/39), fungi 15.4% (6/39), and viruses 2.6% (1/39). Notably, viral sequence LSK-ZM-102022 exhibited similarity to tick phleboviruses, sharing 74.92% nucleotide identity in the RdRp gene and 72% in the NP gene with tick-borne phlebovirus (TBPV) from Greece and Romania, respectively. Its RNA-dependent RNA polymerase (RdRp) encoding region carried conserved RdRp and endonuclease domains characteristic of phenuiviridae viruses. Phylogenetic analysis positioned LSK-ZM-102022 in a distinct but lone lineage within tick phleboviruses basal to known species like brown dog tick phlebovirus and phlebovirus Antigone. Pair-wise genetic distance analysis revealed similar findings. This study emphasizes the urgency of further research on the ecology, transmission dynamics, and pathogenic potential of LSK-ZM-102022 and related TBPVs, crucial for local and global preparedness against emerging tick-borne diseases.